County Business Patterns, 1996 (United States): U.S. Summary, State and County Data ([Verlag nicht ermittelbar], 1999)
The total number of business establishments, mid-March employment figures, and first quarter and annual payrolls are supplied in this data collection at the county, state, and national levels. Also provided are data on the number of establishments by employment-size class. Data are provided for most divisions of the economy, including agricultural services, mining, construction, manufacturing, transportation, public utilities, wholesale trade, retail trade, finance, insurance, real estate, and services. However, data are not included for agricultural production, railroad, government, or household employment.